Lupus nephritis in Latin American patients: 10-year results from a single medical center in Argentina. (February 2016) - Vinicki, J P; Paniego, F M; De Rosa, G; Dubinsky, D; Laborde, H A; Marini, A; Nasswetter, G
Introduction: Several studies have shown that Hispanic patients generally experience a worse renal prognosis than non-Hispanic white patients with lupus. To date, there is no report on American College of Rheumatology (ACR) renal response criteria (ACR-RRC) in patients from Latin America. Objective: To evaluate treatment response in patients with proliferative and membranous lupus nephritis (LN) according to ACR-RRC. Methods: A retrospective study (2001–2011) was performed in our hospital and the data collected included clinical information, renal assessment and immunological parameters. Details related to treatment received during induction and maintenance therapy were also recorded. Results: The study included forty-three Latin American patients (37 women) from Argentina. Mean follow-up was 54 months. The regimen used for induction therapy included intravenous cyclophosphamide (IV-CYC) for six months in 36 patients and only seven received mycophenolate mofetil (MMF) given twice daily for a total dose of 2.5 ± 0.5 grams a day. For the maintenance period, six patients continued with quarterly IV-CYC, 20 patients received MMF (1.5 ± 0.5 grams a day) and 17 patients received azathioprine (AZA) 1.5 – 2 mg/kg/day. ACR-RRC observed after induction therapy was complete response in 19%, partial response in 9%, improvement in 42%, unchanged in 14%, and 16% had deterioration despite treatment. ACR-RRC observed after maintenance therapy was complete response in 30%, partial response in 23%, improvement in 19%, unchanged in 16%, and 12% had deterioration. Relapse was observed in 11 patients (25%). Ten out of 11 cases (91%) who relapsed did not achieve a complete response at the end of the induction therapy. Conclusion: In Latin American patients from Argentina, only 19% could achieve a complete response after induction therapy and 30% achieved a complete response after maintenance therapy. Failing to obtain a complete response after induction therapy was related to an increased risk of relapse during long-term follow-up in our study.